2018
DOI: 10.1007/s00406-018-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid markers analysis in the differential diagnosis of dementia with Lewy bodies and Parkinson’s disease dementia

Abstract: Dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) share a couple of clinical similarities that is often a source of diagnostic pitfalls. We evaluated the discriminatory potential of brain-derived CSF markers [tau, p-tau (181P), Aβ, NSE and S100B] across the spectrum of Lewy body disorders and assessed whether particular markers are associated with cognitive status in investigated patients. The tau CSF level, amyloid β and p-tau/tau ratio were helpful in the distinction between DLB and PDD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
1
17
0
2
Order By: Relevance
“…We observed increased levels of GFAP, S100B and MBP, but not of NSE, in CSF of PD in comparison to controls. These results are partly in agreement with previous studies, showing no differences in S100B and NSE levels in serum [21] and in CSF [22] between PD and controls. Yet, other studies reported no significant differences in CSF GFAP levels between PD and controls [9,23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed increased levels of GFAP, S100B and MBP, but not of NSE, in CSF of PD in comparison to controls. These results are partly in agreement with previous studies, showing no differences in S100B and NSE levels in serum [21] and in CSF [22] between PD and controls. Yet, other studies reported no significant differences in CSF GFAP levels between PD and controls [9,23].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported increased levels of the glial proteins S100B and GFAP in CSF and in serum of patients with dementia, i.e. AD, FTD and dementia with Lewy bodies (DLB) [9,10,22,[25][26][27]. The higher levels in CSF and serum of GFAP and S100B in dementia might indicate an association between glial proteins and cognitive functioning, since S100B levels in CSF [26,28] and in serum [29], and of GFAP in serum [9] and CSF [27] correlated with the severity of cognitive dysfunction in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of dementia associated with CSF tau and p‐tau levels in DLB and CSF tau and p‐tau ratio in PDD. Also, rapid disease course was associated with the decrease of Aβ 1‐42 in DLB . Significantly lower levels of CSF Aβ 1‐42 was found in neuropathologically confirmed DLB cases with Aβ plaques compared to DLB without Aβ plaques .…”
Section: Methodsmentioning
confidence: 86%
“…The sustained microglial activation in PD appears likely to reflect DAMP-mediated activation of certain toll-like receptors (notably TLR2 and TLR4), as well as the receptor of advanced glycation end-products (RAGE), the integrin receptor Mac1, and CD11b [25][26][27][28][29][30][31][32][33][34][35]. Rodent and cell culture studies suggest that HMGB1 (which activates TLR4, RAGE, and Mac1), S100B (primarily of astrocyte origin, also a RAGE ligand), and oligomeric ASYN (a ligand for TLR2 and CD11b) contribute to chronic microglial activation in PD [31,[34][35][36][37][38][39][40][41][42][43]. S100A8, S100A9, and S100A12 also have the potential to activate RAGE in this disorder; RAGE is highly promiscuous in its response to ligands [14,31,[34][35][36][37][38][39][40][41][42][43][44].…”
Section: Targeting Nadph Oxidase-phycocyanobilin/phycocyanin/spirulinamentioning
confidence: 99%
“…Rodent and cell culture studies suggest that HMGB1 (which activates TLR4, RAGE, and Mac1), S100B (primarily of astrocyte origin, also a RAGE ligand), and oligomeric ASYN (a ligand for TLR2 and CD11b) contribute to chronic microglial activation in PD [31,[34][35][36][37][38][39][40][41][42][43]. S100A8, S100A9, and S100A12 also have the potential to activate RAGE in this disorder; RAGE is highly promiscuous in its response to ligands [14,31,[34][35][36][37][38][39][40][41][42][43][44].…”
Section: Targeting Nadph Oxidase-phycocyanobilin/phycocyanin/spirulinamentioning
confidence: 99%